Шляхи забезпечення екологічної безпеки місць зберігання пально-мастильних матеріалів аеропортів - Козловська, Т. Ф.; Kozlovska, T. F.; ORCID: https://orcid.org/0000-0002-6106-5524; Нальотова, Н. І.; Nalotova, N. I.; ORCID: https://orcid.org/0000-0003-3243-202X; Панченко, В. І.; Panchenko, V. I.; ORCID: https://orcid.org/0000-0002-4729-4435; Дрогомерецька, Г. В.; Drohomeretska, H. V.; ORCID: https://orcid.org/0000-0001-8296-9816 (Вісник Херсонського національного технічного університету. – 2021. – № 1 (76). – С. 27-34, 2021)
Розглянуто можливість створення системи моніторингу стану компонентів навколишнього природного середовища – атмосферного повітря, ґрунтів і підземного водного середовища – під час завантаження, перекачування, зберігання пально-мастильних матеріалів на територіях аеропортів при експлуатації вертолітного транспорту. Запропоновано автоматизований комплекс забезпечення екологічної безпеки, придатний для відслідковування рівнів забруднення атмосферного повітря, ґрунтів, підземного водного середовища під час перекачування, зберігання пально-мастильних матеріалів, можливого їх потрапляння до ґрунтів, а потім – до підземних водоносних горизонтів. Відзначено, що більш суттєвого внеску у рівень екологічної небезпеки додають іони важких металів унаслідок інтенсивного техногеннохімічного забруднення територій аеропортів і прилеглих до них ділянок. Установлено ступені екологічного ризику при завантаженні, перекачуванні, зберіганні пально-мастильних матеріалів.

This paper considers the possibility of creating a system for monitoring the state of the components of the environment - atmospheric air, soil and underground water environment - during loading, pumping, storage of fuel and lubricants on the territory of airports during the operation of helicopter transport. An automated complex for ensuring environmental safety is proposed for monitoring the levels of pollution of atmospheric air, soils, underground aquifers during loading, pumping, storage of fuel and lubricants, their possible entry into the ground, and then through underground waters into the surface water layers. Taking into account the quantitative and qualitative characteristics of fuel and lubricants, indicators of harmful effects have been established in case of accidental intake of fuel and lubricants in the components of the environment. It was found that the greatest contribution to the level of environmental hazard is made by heavy metal ions due to intensive technogenic and chemical pollution of airport territories and adjacent areas. The degree of environmental risk during loading, pumping, storage of fuel and lubricants has been determined. The research resulted in an approach to the monitoring and management of technogenic and ecological risk and ecological safety of the components of the natural environment. A structural diagram of an automated complex for ensuring the environmental safety of the air and water environment has been developed, which monitors and informs about the state of the corresponding components of the environment in the territories of airports during the operation of helicopter transport using the mobile communication system (Global System for Mobile Communications GSM).

Рассмотрена возможность создания системы мониторинга состояния компонентов окружающей природной среды – атмосферного воздуха, грунтов и подземной водной среды – при загрузке, перекачке, хранении топливно-смазочных материалов на территориях аэропортов при эксплуатации вертолëтного транспорта. Предложен автоматизированный комплекс обеспечения экологической безопасности для отслеживания уровней загрязнения атмосферного воздуха, грунтов, подземных водоносных горизонтов при загрузке, перекачке, хранении топливно-смазочных материалов, возможного их поступления в грунт, а затем через подземные воды в поверхностные водные слои. С учетом количественных и качественных характеристик топливно-смазочных материалов установлены показатели вредного влияния при случайном поступлении топливно-смазочных материалов в составляющие окружающей природной среды. Выяснено, что наибольший вклад в уровень экологической опасности вносят ионы тяжелых металлов вследствие интенсивного техногенно-химического загрязнения территорий аэропортов и прилегающих к ним участков. Установлены степени экологического риска при загрузке, перекачивании, хранении топливно-смазочных материалов.
Ways to ensure air and water security at airport fuel and lubricants storage
Пути обеспечения экологической безопасности в местах хранения топливно-смазочных материалов аэропортов
Козловська, Т. Ф. Шляхи забезпечення екологічної безпеки місць зберігання пально-мастильних матеріалів аеропортів / Т. Ф. Козловська, Н. І. Нальотова, В. І. Панченко, Г. В. Дрогомерецька // Вісник Херсонського національного технічного університету. – 2021. – № 1 (76). – С. 27-34. - DOI:https://doi.org/10.35546/kntu2078-4481.2021.1.3.
Keywords: Екологічне право. Environmental law. Экологическое право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; екологічна безпека; ecological safety; экологическая безопасность; пально-мастильні матеріали; fuels and lubricants; горюче-смазочные материалы; екологічний ризик; environmental risk; экологический риск; аеропорти; airports; аэропорты; моніторинг; monitoring; мониторинг; автоматизована система; automated system; автоматизированная система